Physiological parameters for Prognosis in Abdominal Sepsis (PIPAS) Study: a WSES observational study - Sartelli, Massimo; Abu-Zidan, Fikri M; Labricciosa, Francesco M; Kluger, Yoram; Coccolini, Federico; Ansaloni, Luca; Leppäniemi, Ari; Kirkpatrick, Andrew W; Tolonen, Matti; Tranà, Cristian; Regimbeau, Jean-Marc; Hardcastle, Timothy; et al. (World journal of emergency surgery, 2019)
BACKGROUND: Timing and adequacy of peritoneal source control are the most important pillars in the management of patients with acute peritonitis. Therefore, early prognostic evaluation of acute peritonitis is paramount to assess the severity and establish a prompt and appropriate treatment. The objectives of this study were to identify clinical and laboratory predictors for in-hospital mortality in patients with acute peritonitis and to develop a warning score system, based on easily recognizable and assessable variables, globally accepted. METHODS: This worldwide multicentre observational study included 153 surgical departments across 56 countries over a 4-month study period between February 1, 2018, and May 31, 2018. RESULTS: A total of 3137 patients were included, with 1815 (57.9%) men and 1322 (42.1%) women, with a median age of 47 years (interquartile range [IQR] 28-66). The overall in-hospital mortality rate was 8.9%, with a median length of stay of 6 days (IQR 4-10). Using multivariable logistic regression, independent variables associated with in-hospital mortality were identified: age > 80 years, malignancy, severe cardiovascular disease, severe chronic kidney disease, respiratory rate ≥ 22 breaths/min, systolic blood pressure < 100 mmHg, AVPU responsiveness scale (voice and unresponsive), blood oxygen saturation level (SpO2) < 90% in air, platelet count < 50,000 cells/mm3, and lactate > 4 mmol/l. These variables were used to create the PIPAS Severity Score, a bedside early warning score for patients with acute peritonitis. The overall mortality was 2.9% for patients who had scores of 0-1, 22.7% for those who had scores of 2-3, 46.8% for those who had scores of 4-5, and 86.7% for those who have scores of 7-8. CONCLUSIONS: The simple PIPAS Severity Score can be used on a global level and can help clinicians to identify patients at high risk for treatment failure and mortality.
Keywords: Abdomen; Chi-Square Distribution; logistické modely; Humans; břicho; lidé středního věku; Injury Severity Score; Sepsis; Early warning score; Female; rizikové faktory; Aged; dospělí; sepse; senioři; lidé; skóre závažnosti úrazu; mortalita v nemocnicích; rozdělení chí kvadrát; Adult; ženské pohlaví; Male; Middle Aged; Emergency surgery; prognóza; Source control; Hospital Mortality; mužské pohlaví; Logistic Models; Prognosis; Risk Factors; Acute peritonitis